The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/microorganisms11081974
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk—Cellulose-Based Agricultural Waste Enhances the Degradation of Synthetic Dyes Using Multiple Enzyme-Producing Extremophiles

Abstract: The brightly colored synthetic dyes used in the textile industry are discharged at high concentrations—for example, various azo dyes including Methylene Blue (MB) and Methyl Orange (MO)—which is a matter of global concern, as such dyes are harmful to humans and the environment. Microbial degradation is considered an efficient alternative for overcoming the disadvantages of conventional physical and chemical dye removal methods. In this study, we investigated the potential of multiple types of the enzyme-produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Rice husk adsorbents and adsorbed contaminants can be regenerated, and biocatalyst immobilization on rice husks is a promising approach. Other studies have also shown that rice husks can be used to remove contaminants such as arsenic, humic acids, phenols, and leachate of municipal solid waste landfills [7]. Rice husk biochar has been found to remove organic or inorganic toxins from waste, reducing environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk adsorbents and adsorbed contaminants can be regenerated, and biocatalyst immobilization on rice husks is a promising approach. Other studies have also shown that rice husks can be used to remove contaminants such as arsenic, humic acids, phenols, and leachate of municipal solid waste landfills [7]. Rice husk biochar has been found to remove organic or inorganic toxins from waste, reducing environmental pollution.…”
Section: Introductionmentioning
confidence: 99%